2001
DOI: 10.4088/pcc.v03n0105
|View full text |Cite
|
Sign up to set email alerts
|

SSRI Antidepressant Medications

Abstract: Side effects of antidepressants can be predicted by receptor selectivity and site of action. Although the selective serotonin reuptake inhibitors (SSRIs) have better overall safety and tolerability than older antidepressants, broad-based experience with SSRIs has shown the frequency and type of side effects to be increased relative to clinical trial data. The author explores the reasons for the different profiles and discusses adverse effects, especially sexual dysfunction, weight gain, and sleep disturbance, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
216
3
1

Year Published

2005
2005
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 569 publications
(222 citation statements)
references
References 16 publications
2
216
3
1
Order By: Relevance
“…This may help to minimize adverse effects of fluoxetine like gastrointestinal disturbances (the most frequently reported side effects). 17 Also as hypercholesterolemia has been shown to be associated with non-response or resistance to antidepressants, statins by reducing cholesterol levels can also improve outcome in patients of resistant depression.…”
Section: Discussionmentioning
confidence: 99%
“…This may help to minimize adverse effects of fluoxetine like gastrointestinal disturbances (the most frequently reported side effects). 17 Also as hypercholesterolemia has been shown to be associated with non-response or resistance to antidepressants, statins by reducing cholesterol levels can also improve outcome in patients of resistant depression.…”
Section: Discussionmentioning
confidence: 99%
“…2 The treatment of depression was revolutionized in 1988 with the approval of fluoxetine, the first serotonin-selective reuptake inhibitor (SSRI), in the United States. 3 Despite the improvements in safety and tolerability made by the advent of this and other SSRIs, these agents have been associated with a number of negative side effects, including sexual dysfunction, weight gain, nausea, insomnia, and somnolence. 3 As such, there remains a serious unmet medical need that awaits the identification of new pharmacological approaches for the treatment of depression.…”
Section: Introductionmentioning
confidence: 99%
“…[4] The National Institute for Health and Care Excellence (NICE) treatment guideline 2015 and other studies recommend generic SSRI as a first-choice drug for adults with depression and generalized anxiety disorder due to its favorable risk-benefit ratio. [5][6][7] It was also found that fewer patients taking SSRI discontinued therapy compared to patients on TCAs that are prone to adverse effects. [8][9][10] The most current Standard Treatment Guideline (STG) in Nigeria (2008) recommends TCAs and SSRIs for treatment of depression.…”
Section: Introductionmentioning
confidence: 99%